BUDGETARY TRANSPARENCY, E-GOVERNMENT AND CORRUPTION: NEW EVIDENCE FROM PANEL DATA APPROACH - YILDIZ, Fazlı; SAGDIC, Ersin Nail; TUNCER, Guner (Ecoforum Journal, 2017)
The effect of transparency indicators on corruption such as budget transparency, e-government, and regulation quality has received considerable attention in recent years. This paper gives some new evidence on this issue using an indicator of open budget index, e-government index and, regulatory quality as transparency indicators. From this perspective, this paper estimates the impact of regulatory quality, e-government index and, open budget index on corruption using unbalanced panel data analysis for selected 48 countries over the period of 2004 to 2015. The results of the analysis reveal that regulatory quality, budget transparency, and e-government indexes have positive and statistically significant effect on corruption.